Spatial Heterogeneity as a Key Variable Influencing Spring-Summer Progression in UVR and PAR Transmission Through Arctic Sea Ice - Matthes, Lisa C.; Mundy, C. J.; L.-Girard, S.; Babin, M.; Verin, G.; Ehn, J. K. (Frontiers in Marine Science, 2020)
The transmission of ultraviolet (UVR) and photosynthetically available radiation (PAR) through sea ice is a key factor controlling under-ice phytoplankton growth in seasonally ice-covered waters. The increase towards sufficient light levels for positive net photosynthesis occurs concurrently with the sea ice melt progression in late spring when ice surface conditions shift from a relatively homogeneous high-albedo snow cover to a less reflective mosaic of bare ice and melt ponds. Here, we present a detailed dataset on the spatial and temporal progression of transmitted UVR and PAR in relation to changing quantities of snow, sea ice and melt ponds. Data were collected with a remotely operated vehicle (ROV) during the GreenEdge landfast sea ice campaign in June-July 2016 in southwestern Baffin Bay. Over the course of melt progression, there was a 10-fold increase in spatially averaged UVR and PAR transmission through the sea ice cover, reaching a maximum transmission of 31% for PAR, 7% for UVB and 26% for UVA radiation. The depth under the sea ice experiencing spatial variability in light levels due to the influence of surface heterogeneity in snow, white ice and melt pond distributions increased from 7 +/- 4 to 20 +/- 6 m over our study. Phytoplankton drifting in under-ice surface waters were thus exposed to variations in PAR availability of up to 43%, highlighting the importance to account for spatial heterogeneity in light transmission through melting sea ice. Consequently, we demonstrate that spatial averages of PAR transmission provided more representative light availability estimates to explain under-ice bloom progression relative to single point irradiance measurements during the sea ice melt season. Encouragingly, the strong dichotomy between white ice and melt pond PAR transmittance and surface albedo permitted a very good estimate of spatially averaged light transmission from drone imagery of the surface and point transmittance measurements beneath different ice surface types.